Ethiopian labour migration to the gulf and South Africa - Asnake Kefale, 1970-; Mohammed, Zerihun (Addis Ababa : Forum For Social Studies, 2016)
The major objective of the research is to produce evidence-based knowledge on the social and economic impacts of labour migration by looking at the challenges and opportunities of Ethiopian labour migration to the Gulf and South Africa. On the one hand, international migration from Ethiopia could be considered as an aspect of development problem. The major push factors that forces Ethiopian migrants to the Gulf and South Africa are economic/developmental problems ranging from lack of employment opportunities to wage differentials. On the other hand, international migration could be considered as an important resource that could be tapped for accelerating socio-economic development. At the general level, this research aims to examine the successes and failures of policies and institutions in realising the potentials of international migration for socio-economic development of the country and minimizing its adverse impacts. At the same time, the growing problem of illegal migration will be examined.
1. Introduction -- 2. International migration, trafficking, smuggling and mixed migration -- 3. Ethiopian labour migration to the Gulf -- 4. Ethiopian irregular migration to South Africa -- 5. Conclusion and ways forward.
Includes bibliographical references.
Keywords: Labor mobility -- Ethiopia; Foreign workers, Ethiopian -- South Africa; Foreign workers, Ethiopian -- Persian Gulf Region; Ethiopia -- Emigration and immigration -- Social aspects; Ethiopia -- Emigration and immigration -- Economic aspects